2021
DOI: 10.1021/acsnano.1c05266
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Biophotonic Lasing Network Driven by Amyloid Fibrils in Microcavities

Abstract: Self-assembled biological structures have played a significant role in many living systems for its functionality and distinctiveness. Here, we experimentally demonstrate that the random dynamic behavior of strong light–matter interactions in complex biological structures can provide hidden information on optical coupling in a network. The concept of biophotonic lasing network is therefore introduced, where a self-assembled human amyloid fibril network was confined in a Fabry–Perot optical cavity. Distinctive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The mirror cavity provides strong optical feedback that can be used to detect subtle molecular changes in the gain medium. , The advantage of the cavity lasing is also the possibility of studying biomolecules in liquid, which is more convenient than a solid phase for elucidating the influence of external factors on the biomolecule structure. In the case of dye-stained biomolecules, fluorophores act as gain materials in the cavity and are providing information on the biomolecule structure.…”
mentioning
confidence: 99%
“…The mirror cavity provides strong optical feedback that can be used to detect subtle molecular changes in the gain medium. , The advantage of the cavity lasing is also the possibility of studying biomolecules in liquid, which is more convenient than a solid phase for elucidating the influence of external factors on the biomolecule structure. In the case of dye-stained biomolecules, fluorophores act as gain materials in the cavity and are providing information on the biomolecule structure.…”
mentioning
confidence: 99%
“…24,25 Recent studies in biolasers have also demonstrated their capability to detect structural changes in biological gain materials or microcavities. 26,27 For instance, Piotr et al demonstrated amplified stimulated emission with ThT oligomers in solidstate thin films, where different conformations would lead to changes in the lasing threshold. 16 Zhang et al developed a whispering gallery mode (WGM) biolaser by incorporating fluorescein sodium salt into silk fibroin microspheres, and the structural change of the silk fibroin is observed extrinsically from changes of lasing wavelength shifts.…”
mentioning
confidence: 99%
“…Rhodamine 6G (R6G) was used as laser gain in the cavity matrix to observe the physical transformational change as it can bind with insulin protein via electrostatic interactions. 26 Figure 2a shows the underlying resonant mechanism of lasing action in the microdroplet biolaser. The lasing action of the microdroplet resonator exhibits a vertically oriented oscillation arc-like (AL) mode.…”
mentioning
confidence: 99%
See 2 more Smart Citations